2021
DOI: 10.1177/00045632211029327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of paraprotein polymerisation on quantitation by capillary zone electrophoresis and Hevylite®

Abstract: Objectives Up to 3% of patients with monoclonal gammopathies have multiple serum paraproteins. This article investigates whether multiple isotype-matched paraproteins, as seen on capillary zone electrophoresis (CZE), are truly biclonal. Methods Sera containing multiple isotype-matched paraproteins were treated with the reducing agent dithiothreitol (DTT) and CZE performed pre- and post-treatment. Band resolution and effect of resolution on quantitation of paraprotein burden was assessed. The Hevylite® turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The recently published study by Valentine and Dawney 1 contained interesting insights about multiple isotype-matched monoclonal proteins (MIMMP) and the effect of treatment with a reducing agent. Their findings suggested that, in most cases, reducing agent treatment caused IgA but not IgG MIMMP to resolve into a single band.…”
mentioning
confidence: 99%
“…The recently published study by Valentine and Dawney 1 contained interesting insights about multiple isotype-matched monoclonal proteins (MIMMP) and the effect of treatment with a reducing agent. Their findings suggested that, in most cases, reducing agent treatment caused IgA but not IgG MIMMP to resolve into a single band.…”
mentioning
confidence: 99%